Characterization of oil-free and oil-loaded liquid-crystalline particles stabilized by negatively charged stabilizer citrem - Nilsson, Christa (Langmuir : the ACS journal of surfaces and colloids, 2012)
The present study was designed to evaluate the effect of the negatively charged food-grade emulsifier citrem on the internal nanostructures of oil-free and oil-loaded aqueous dispersions of phytantriol (PHYT) and glyceryl monooleate (GMO). To our knowledge, this is the first report in the literature on the utilization of this charged stabilizing agent in the formation of aqueous dispersions consisting of well-ordered interiors (either inverted-type hexagonal (H(2)) phases or inverted-type microemulsion systems). Synchrotron small-angle X-ray scattering (SAXS) and cryogenic transmission electron microscopy (cryo-TEM) were used to characterize the dispersed and the corresponding nondispersed phases of inverted-type nonlamellar liquid-crystalline phases and microemulsions. The results suggest a transition between different internal nanostructures of the aqueous dispersions after the addition of the stabilizer. In addition to the main function of citrem as a stabilizer that adheres to the surface of the dispersed particles, it has a significant impact on the internal nanostructures, which is governed by the following factors: (1) its penetration between the hydrophobic tails of the lipid molecules and (2) its degree of incorporation into the lipid-water interfacial area. In the presence of citrem, the formation of aqueous dispersions with functionalized hydrophilic domains by the enlargement of the hydrophilic nanochannels of the internal H(2) phase in hexosomes and the hydrophilic core of the L(2) phase in emulsified microemulsions (EMEs) could be particularly attractive for solubilizing and controlling the release of positively charged drugs